2007
DOI: 10.1080/13607860601086553
|View full text |Cite
|
Sign up to set email alerts
|

Association between lifestyle activity and depressed mood among home-dwelling older people: A community-based study in Japan

Abstract: In the community-based cross-sectional study, we investigated patterns of lifestyle activities among older people and examined the association between specific types of lifestyle activity and depressed mood status. The participants were 656 men and women aged 65 or older in 2004 who lived in a rural town in Japan, neither institutionalized nor hospitalized and who did not have symptoms of dementia. We found that less interaction with neighbors, society and friends was highly associated with depressed mood for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 37 publications
1
22
1
Order By: Relevance
“…The link between childlessness and loneliness was, however, stronger for women than for men. This seems consistent with the finding of Arai and colleagues that depressed mood was less likely for Japanese older women, but not for men, if they had frequent contact with children and/or grandchildren [21]. The findings presented here thus provide only partial support for Oshio's suggestion that men's wellbeing is more sensitive than women's to the family situation.…”
Section: Discussionsupporting
confidence: 79%
“…The link between childlessness and loneliness was, however, stronger for women than for men. This seems consistent with the finding of Arai and colleagues that depressed mood was less likely for Japanese older women, but not for men, if they had frequent contact with children and/or grandchildren [21]. The findings presented here thus provide only partial support for Oshio's suggestion that men's wellbeing is more sensitive than women's to the family situation.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, avoidance of excess salt and fat in men and moderate alcohol consumption in women were related to prevention of depressive symptoms among them in their later life. Several empirical studies have found that physical exercise positively affects mood (Arai et al 2007;Meeks et al 2007;Williams and Tappen 2008). In addition, lower physical functional capacity is related to depression among elderly people (Lee and Shinkai 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found in the present study that being together with grandchildren and great grandchildren was a way to be stimulated and cheered up. According to Arai et al (2007), social interactions within the society, neighbors, family, and friends are of importance for preventing depressive moods. Furthermore, Chiu and Spencer (2010) found that living an active social life have positive impacts on older people's health status.…”
Section: Discussionmentioning
confidence: 99%